Effects of Flunixin Meglumine on Oxidant and Antioxidant System after Disbudding with Caustic Paste in Calves - Yakan, Selvinaz; Duzguner, Vesile; Aksoy, Ozgur (Acta Scientiae Veterinariae, 2018)
Background: Disbudding is often practiced in modern farm because of the reasons for the safekeeping of the animal, other animals lessen the risk of injury and less aggressive behavior. Without regard to the method of disbudding leads to disruption behavioral changes, cardiac and endocrine responses related pain of animals. Sedation, local anesthesia and analgesia are performed studies in order to eliminate of cardiac, endocrine, behavioral response which is caused by pain associated with disbudding. In this study, it was aimed to determine the effect on the oxidant and antioxidant system in the calves of disbudding by using the caustic paste with and without painkiller. Materials, Methods & Results: The animal material of the study was created 24 Simmentals calves in different sexes on average 2 weeks (± 2 days) and 50 kg (± 15 kg) live weight. The cases were randomly divided into 2 groups of 12 calves in each group. In the group I (analgesia group); caustic paste+painkiller (2.2 mg-1 flunixin meglumine intravenous, IV) and group II (non-analgesia group); as disbudding applied with caustic pasta application only were divided into 2 groups. In the I group, 15th min before the application, flunixin meglumine at a dose of 2.2 mg-1 was administered IV and the horn blunting was performed by caustic paste method. Blood samples were taken at 15, 30 and 60th min after completion of horn blunting and physiological findings were recorded. In group II, the horns of the calves were disbudding with the same technique (but no analgesia aplication). Blood samples were taken at 15, 30 and 60th min after completion of horn blunting and physiological findings were record. Cortisol, glucose, total oxidant capacity (TOC) and total antioxidant capacity (TAC), 8-hydroxy-2’-deoxyguanosine (8-OHdG), glutathione (GSH), superoxide dismutase (SOD) enzymes measurements (ELISA) were performed in both groups. TOC and TAC tests were used to determine the oxidative stress index in the obtained serum, 8-OHdG measurement which is the most sensitive and most frequent oxidative DNA damage indicator for determination of oxidative damage; GSH, SOD enzymes were analyzed by ELISA using commercial kit for the evaluation of antioxidant potential. For evaluation of pain in animals, cortisol (ELISA) and glucose level in serum were measured with ELISA by using commercial kit. In the group without flunixin meglumine, cortisol was increased significantly from the 15th min (P < 0.05), but there was no increase in the 30 and 60th min in painkiller administered group. Glucose levels were higher in the group not using painkillers than those used at 15th (P < 0.001) and 30, 60th min (P < 0.05). TOC (P < 0.001) and 8-OHdG (P < 0.05) values were significantly higher in the group without painkiller while TAC, GSH and SOD levels (P < 0.05) were significantly decreased. Discussion: It has been observed that sedation (such as xylazine) and local anesthesia (such as lidocaine) use removed pain-induced stress in the disbudding with caustic paste in calves. However, in order to remove the endocrine response, it is necessary to combine the anesthesia protocol with the analgesic (such as flunixin meglumine) combination. According to our results concluded that the painkiller given before the disbudding process was supporting the antioxidant system, reducing the level of cortisol and oxidative stress.